Coordination of lower extremity multi-joint control strategies during the golf swing - Peterson, T. J.; McNitt-Gray, J. L. (Journal of Biomechanics, 2018)
This study aimed to understand how players coordinate the multi-joint control strategies of the rear and target legs to satisfy the lower extremity and whole-body mechanical objectives during the golf swing when hitting shots with different clubs. Highly skilled golf players (n = 10) performed golf swings with a 6-iron and a driver. Joint kinetics were calculated using ground reaction forces and segment kinematics to determine net joint moments (NJMs) during the interval of interest within the downswing. Between club difference in NJMs and 3D support moments were compared across the group and within a player. Although player-specific multi-joint control strategies arose, players generally increased target leg ankle, knee, and hip NJMs when hitting with the driver while maintaining the relative contribution to the 3D support moment. Multi-joint control strategies used to control the target and rear legs were found to be different, yet the majority of the 3D support moment was produced by NJMs about an axis perpendicular to the leg planes. These results emphasize the importance of recognizing how an individual player coordinates multi-joint control from each leg, and highlights the need to design interventions that are player and leg specific to aid in improving player performance.